KAMPANYE LINGKUNGAN DALAM NOVEL TANGIS REMBULAN DI HUTAN BERKABUT KARYA S. PRASETYO UTOMO BAGI SISWA JENJANG PENDIDIKAN DASAR - Andrian, Setia Naka; Rifai, Ahmad (ALAYASASTRA, 2017)
This research is descriptive qualitative research. Aiming for environmental campaigns on students at elementary education level. Specific targets of related research on social issues on environmental preservation through the values of the story in a novel presented in Indonesian language subjects. The method used in this research is literature method with qualitative approach. Various problems that occur in the life of the community campaigned to students through the separation of a novel. The environmental campaigns presented through a literary work can be accepted by students. Expected to grow the soul of a generation of nations who feel have their environment.Keywords: social communication, green literature, environmental campaigns.